Immunoturbidimetric assays for serum apolipoproteins A1 and B using Cobas Bio centrifugal analyser. Issue 4 (April 1988) - Mount, J N; Kearney, E M; Rosseneu, M; Slavin, B M
Abstract : Immunoturbidimetric assays for measuring the apolipoproteins A1 and B using the Cobas Bio centrifugal analyser are described. The methods were specific, offered good sensitivity (less than 0.05 g/l) and intrabatch variability, with coefficients of variation between 2.4% and 3.5%, and were cost effective. Reference ranges were calculated for a group of civil servants, aged 35 to 55 years.